2007
DOI: 10.2165/00044011-200727110-00001
|View full text |Cite
|
Sign up to set email alerts
|

Updated Meta-Analytical Approach to the Efficacy of Antihypertensive Drugs in Reducing Blood Pressure

Abstract: This new analysis supports the results of the earlier investigation, in that indapamide SR 1.5 mg/day appeared to be the most effective drug for producing significant reductions in SBP within 8-12 weeks, which is an essential element in optimising cardiovascular prevention among hypertensive patients. The clinical application of these results should take into consideration all the limitations discussed in this analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 4 publications
4
31
0
11
Order By: Relevance
“…28 Efficacy of antihypertensive drugs in reducing BP analysed by meta-analytical approach also revealed that telmisartan provided numerically greater weighted average reductions of DBP and SBP than enalapril and ramipril, which paralleled our findings. 10 The findings of ONTARGET showed that telmisartan was equivalent to ramipril in the patients with vascular diseases or high-risk diabetes. However, telmisartan monotherapy might show an increase in benefits to patients with hypertension in the long run with its better lowering BP effect, without the interference of so many other antihypertensive drugs in the ONTARTGET.…”
Section: O000001mentioning
confidence: 99%
See 1 more Smart Citation
“…28 Efficacy of antihypertensive drugs in reducing BP analysed by meta-analytical approach also revealed that telmisartan provided numerically greater weighted average reductions of DBP and SBP than enalapril and ramipril, which paralleled our findings. 10 The findings of ONTARGET showed that telmisartan was equivalent to ramipril in the patients with vascular diseases or high-risk diabetes. However, telmisartan monotherapy might show an increase in benefits to patients with hypertension in the long run with its better lowering BP effect, without the interference of so many other antihypertensive drugs in the ONTARTGET.…”
Section: O000001mentioning
confidence: 99%
“…7 Telmisartan 80 mg given once daily provides a better BP control than losartan 50 mg or valsartan 80 mg. 8,9 Telmisartan provides numerically greater weighted average reductions of diastolic BP (DBP) and systolic BP (SBP) than irbesartan and candesartan cilexetil. 10 The findings of the Ongoing Telmisartan Alone and in Combination with Ramipril Global Endpoint Trial (ONTARGET) show that the combination of telmisartan with ramipril is associated with more adverse events without an increase in benefits in patients with vascular disease or high-risk diabetes. 11 Aiming to evaluate which drug was more eligible for patients with hypertension, we undertook a systematic review and meta-analysis to determine the clinical efficacy and tolerability of telmisartan in comparison with ACEIs as monotherapy in the treatment of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Una metanalisi di più recente pubblicazione ha analizzato 80 trial clinici per un totale di 10.818 pazienti [17]. Per essere inclusi nell'analisi i trial dovevano valutare l'effetto antipertensivo di un farmaco in pazienti con ipertensione essenziale da lieve a moderata (sistolica 140-179 mmHg e/o diastolica 90-109 mmHg).…”
Section: Efficacia Clinica Comparataunclassified
“…Una possibilità in questo senso ci è fornita dai risultati emersi dalla metanalisi, precedentemente illustrata, condotta da Baguet e colleghi [17]. Fra i dati riportati da Baguet sono state individuate le dosi dei diversi bloccanti dei recettori per l'angiotensina in grado di dare riduzioni pressorie medie sovrapponibili e, sulla base di tali dosaggi, sono stati calcolati i costi giornalieri (Tabella X).…”
Section: Costi DI Terapia Ponderati Per L'efficaciaunclassified
“…Согласно мета-анализу 80 рандомизи-рованных контролируемых исследований с участием 10 818 пациентов, индапамид ретард в дозе 1,5 мг в сутки продемонстрировал наибольшее снижение систолического АД не только среди диуретиков, но и среди всех 16 антигипертензивных препаратов раз-личных классов, включенных в данный мета-анализ [7]. Результаты рандомизированного двойного сле-пого плацебо-контролируемого исследования X-CELLENT продемонстрировали способность инда-памида ретард не только эффективно снижать систо-лическое АД, но и уменьшать пульсовое АД, являющееся важным и независимым фактором риска развития сердечно-сосудистых осложнений при ИСАГ у пожилых [8].…”
unclassified